KORELASI KECEPATAN DAN KELINCAHAN DENGAN KEMAMPUAN DRIBBLING PEMAIN SEPAK BOLA - Sabdiming, Petrus Peardy; Perdana, Rahmat Putra; Rubiyatno, Rubiyatno (Universitas Tanjungpura, 2025)
The purpose of this study is to examine the connection between soccer players' dribbling abilities and their speed and agility. Twenty students from Tanjungpura University's PKO soccer study program made up the research sample. They were put through a 30-meter running agility test with a ball, a shuttle run, and a speed test dribbling test with the ball acting as a barrier. Tests for homogeneity, correlation, and normality were employed to examine the information.. The null hypothesis (H₀) was approved since the normality test's p-value was greater than 0.05. p-value in the homogeneity test was greater than 0.05, and the correlation test revealed a very strong and positive correlation with a value over 0.95 that at the 0.01 (1%) level was significant. The results of the investigation show a significant positive association between ball dribbling ability and speed and agility. These results imply that soccer players' dribbling skills can be enhanced by boosting speed and agility.